2020
DOI: 10.1111/oik.06910
|View full text |Cite
|
Sign up to set email alerts
|

Water restriction induces behavioral fight but impairs thermoregulation in a dry‐skinned ectotherm

Abstract: Behavioral fight responses to desiccation risk are important to predict the vulnerability of terrestrial animals to climate change and yet, they have received little attention so far. In terrestrial ectotherms, behavioral regulation of the water balance (i.e. hydroregulation) is likely to be plastic and may tradeoff with thermoregulation behavior because water loss rates are generally higher in warmer environments and body temperatures. When low water availability and heat stress cause physiological dehydratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 57 publications
3
35
1
1
Order By: Relevance
“…The analysis of daily thermoregulation patterns reveals subtler effects of water conditions. In general, lizards bask at higher temperatures at the beginning than at the end of the day, as highlighted in our previous work using the same protocol with a thermal gradient [40,46] or with more complex experimental arenas [30]. The effects of free-standing water availability are more pronounced at the end of the day than at the beginning: in the presence of free water, lizards maintain a higher preferred temperature that is more stable over time during the day, whereas a decrease in body temperatures is observed at the end of the day under water restriction conditions, especially in females (effect size of ca.…”
Section: Plos Onementioning
confidence: 68%
See 4 more Smart Citations
“…The analysis of daily thermoregulation patterns reveals subtler effects of water conditions. In general, lizards bask at higher temperatures at the beginning than at the end of the day, as highlighted in our previous work using the same protocol with a thermal gradient [40,46] or with more complex experimental arenas [30]. The effects of free-standing water availability are more pronounced at the end of the day than at the beginning: in the presence of free water, lizards maintain a higher preferred temperature that is more stable over time during the day, whereas a decrease in body temperatures is observed at the end of the day under water restriction conditions, especially in females (effect size of ca.…”
Section: Plos Onementioning
confidence: 68%
“…It also explains why overall effects of our manipulation on thermal preference were generally small since experiments lasted only one day, an insufficient time to induce a severe dehydration. Other studies have shown that changes in thermoregulation and activity were proportional to the dehydration status of individuals in several species of reptiles [29,30,34]. In contrast, Sannolo and Carretero [28] observed short-term behavioral responses to water restriction suggesting that Podarcis lizards might be sensitive to the perception of dehydration risk.…”
Section: Plos Onementioning
confidence: 95%
See 3 more Smart Citations